2021
DOI: 10.1017/s000711452100091x
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina supplementation during gradual weight loss in competitive wrestlers

Abstract: We aimed to assess the effects of spirulina supplementation during gradual weight loss on serum concentrations of follistatin (FST), myostatin (MST), insulin-like growth factor 1 (IGF-1), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and body composition in competitive wrestlers. Forty competitive wrestlers (age: 22 ± 2 years) were randomly assigned to one of two groups: gradual weight loss + spirulina (SP; n=20) or gradual weight loss + placebo (PL; n=20). Subjects in both groups lost weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Additional benefits of spirulina supplementation in their study were demonstrated by Bagheri et al. (2021). Forty professional wrestlers participated in the study.…”
Section: Algae Proteinsmentioning
confidence: 54%
See 2 more Smart Citations
“…Additional benefits of spirulina supplementation in their study were demonstrated by Bagheri et al. (2021). Forty professional wrestlers participated in the study.…”
Section: Algae Proteinsmentioning
confidence: 54%
“…Kalpana et al (2017) showed that spirulina supplementation at a dose of 3 g day À1 could improve cardiorespiratory performance through improved recovery, reduced fatigue, and reduced exercise-induced lipid peroxidation, the similar extent to commercially available antioxidants. Additional benefits of spirulina supplementation in their study were demonstrated by Bagheri et al (2021). Forty professional wrestlers participated in the study.…”
Section: Algae Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the identification of alternative adiposity-reducing strategies with the potential to prevent or alleviate the negative consequences of obesity is warranted. Apart from lifestyle modification, often considered the cornerstone of a weight management programme (4)(5)(6) , a wide range of supplements are now available touting anti-obesity properties (7)(8)(9)(10) . Among those, conjugated linoleic acid (CLA) has shown promise as a food supplement to reduce adiposity in preventing overweightness and obesity (11,12) .…”
mentioning
confidence: 99%